2006
DOI: 10.1002/adma.200600977
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Networks: Sensing of Distributed Strain and Damage for Life Prediction and Self Healing

Abstract: Conducting carbon nanotube networks formed in an epoxy polymer matrix can be utilized as highly sensitive in situ sensors for detecting the onset, nature, and evolution of damage in advanced polymer‐based composites using direct‐current measurements (see figure). These results hold promise for evaluation of autonomic self‐healing approaches for polymers and for the development of enhanced life‐prediction methodologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
349
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 605 publications
(367 citation statements)
references
References 39 publications
7
349
0
Order By: Relevance
“…Since its commercialization in 1981, many studies have been reported on the structural [12], thermal [13] and mechanical [14] characterization of this high-performance thermoplastic material. In the literature there are many reports related to the integration of SWCNTs into polymer matrices [15,16], but only a few papers deal with such composites with a PEEK matrix; the most relevant being those published by Shaffer and co-workers [17,18], working with carbon nanofibres/PEEK composites and by Baaba et al [19], dealing with multi-walled nanotubes functionalized with sulfonated PEEK.…”
mentioning
confidence: 99%
“…Since its commercialization in 1981, many studies have been reported on the structural [12], thermal [13] and mechanical [14] characterization of this high-performance thermoplastic material. In the literature there are many reports related to the integration of SWCNTs into polymer matrices [15,16], but only a few papers deal with such composites with a PEEK matrix; the most relevant being those published by Shaffer and co-workers [17,18], working with carbon nanofibres/PEEK composites and by Baaba et al [19], dealing with multi-walled nanotubes functionalized with sulfonated PEEK.…”
mentioning
confidence: 99%
“…They incorporate the trial of uniting polymer science, exploratory and consistent mechanics, and composites taking care of principles. The best systems will be crossbreed techniques which navigate the various lengths and time sizes of the particular philosophies [44].…”
Section: Economics and Future Outlooksmentioning
confidence: 99%
“…The development of novel glass fibre reinforced plastics (GFRPs) with electrical conductivity has opened up new opportunities in which unique functionality can be added to existing material systems for a broad range of applications, including electrostatic dissipation, electric field shielding, damage detecting, etc. As pilot approach, the electrical conductivity of GFRPs has been achieved by either adding conductive particles, such as carbon blacks and carbon nanotubes (CNTs) in polymer matrix, or composite surface treated with antistatic or metallic coatings (Thostenson et al, 2006, 2008, Böger et al, 2008. As outstanding multifunctional sensing materials, recently, CNTs have stimulated the development of various conductive nanotube/polymer composites with sensitive features to piezoresistivity, temperature and moisture (Baughman et al, 2002;Bekyarova et al, 2007;Veedu et al, 2006;Dzenis, 2008).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The GFRPs with carbon blacks and MWCNTs in polymer matrix with health monitoring functionality have recently been successfully developed to monitor damage initiation and evolution. Thostenson and Chou processed GFRPs with embedded CNTs in epoxy matrix to evaluate the onset and evaluation of damage (Thostenson et al, 2006(Thostenson et al, , 2008. One outstanding challenge is to fabricate in-situ sensing composite materials at micrometer scale, especially at interphase of composites Zhang et al, 2010), being capable of detecting stress/strain, temperature and humidity with high sensitivity.…”
Section: Wwwintechopencommentioning
confidence: 99%